2021
DOI: 10.1002/smll.202102792
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Energy Gap between Band‐Edge and Trap States Slows Down Picosecond Carrier Trapping in Highly Luminescent InP/ZnSe/ZnS Quantum Dots

Abstract: Non‐toxic InP‐based nanocrystals have been developed for promising candidates for commercial optoelectronic applications and they still require further improvement on photophysical properties, compared to Cd‐based quantum dots (QDs), for better device efficiency and long‐term stability. It is, therefore, essential to understand the precise mechanism of carrier trapping even in the state‐of‐the‐art InP‐based QD with near‐unity luminescence. Here, it is shown that using time‐resolved spectroscopic measurements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…As shown in Fig. 3c , the TA spectra of InP/ZnSe 0.7 S 0.3 /ZnS exhibited a slight shift of peaks for both PA and PB, which confirmed the restrain of the interface defects and featured layered quantum-well structure 41 , 45 47 . While the inner shell was tuned to InP/ZnSe/ZnS QDs as shown in Fig.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…As shown in Fig. 3c , the TA spectra of InP/ZnSe 0.7 S 0.3 /ZnS exhibited a slight shift of peaks for both PA and PB, which confirmed the restrain of the interface defects and featured layered quantum-well structure 41 , 45 47 . While the inner shell was tuned to InP/ZnSe/ZnS QDs as shown in Fig.…”
Section: Resultsmentioning
confidence: 61%
“…In the light of Fermi golden rule, the PL lifetime was in reverse proportion with the overlap of electron and hole functions 43 . As a result, the fast decay process was considered as band-edge emission because of the large overlap of electrons and holes whereas the slow decay process was considered as trap emission 41 , 44 . With the increasing ratio of Se/S element of ZnSe x S 1−x inner shell, the ratio of trap/band-edge emission gradually decreased from 40% to 14% until x = 0.7, then the ratio of trap/band-edge emission rose again (Table S4 in Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work found that the shallow trap states are close to the conduction band edge and act as electron traps. [32] Here, the total PL QY was not strongly reliant on electron trapping. We ascertained that, in our case, the shell morphology control affects the PL QY as well as both hot hole trapping and electron trapping.…”
Section: Transient Absorption Spectroscopy and Hot Hole Trappingmentioning
confidence: 89%
“…Sung et al recently revealed that the shallow defect states leading to a partially trap emission in highly luminescent InP/ZnSe/ZnS QDs are associated with indium impurities in the ZnSe shell. [32] Weighting the preexponential factors by their associated lifetime and plotting versus wavelength presents the decay-associated spectra (DAS).…”
Section: Time-resolved Photoluminescence Spectra and The Correspondin...mentioning
confidence: 99%
“…However, the lattice mismatch of the core/shell structure implies more defects and prevents the formation of a perfect heteroepitaxial interface. In addition, broad emission originates from the luminescence of holes trapped by surface and lattice defects, resulting in spectral broadening [ 28 , 117 ]. For narrow linewidth InP QLED, the growth of InP QDs with high lattice integrity, uniformity, and high spherical symmetry is helpful to exhibit more excellent light-emitting properties.…”
Section: Challenge and Future Directionmentioning
confidence: 99%